An analysis of the "follow the money": investigative audit technique in campaign funds for the election of regional heads in Indonesia / Rizal Mawardi ... [et al.] - Mawardi, Rizal; Robby Maulana, Rausanfiker; -, Ridarmelli; Wijayanti, Inung (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2022)
The practice of campaign funds monitoring that is limited to compliance with laws and regulations by submitting reports and audits is still considered insufficient in an effort to realize a clean election and support the implementation of good governance. This research aimed to find out information related to compliance with campaign funds for 2020 Regional Head Elections through the follow the money investigative audit technique in accordance with regulatory provisions as an evaluation of the implementation of the 2020 Regional Head Elections in terms of campaign funds. This research was conducted in the Indonesian Financial Transaction Reports and Analysis Centre (PPATK) as Financial Intelligence Unit using a qualitative method with case studies and descriptive analysis. Based on the results of the analysis and other information owned by PPATK, there were indications of violations of campaign funds regulation as stated in the National Election Commission Regulations Number 12 of 2020 and indication of money politics practice.